Serviceability limits of reinforced concrete hinges. (1st April 2020) - Schlappal, Thomas; Kalliauer, Johannes; Vill, Markus; Gmainer, Susanne; Mang, Herbert A.; Eberhardsteiner, Josef; Pichler, Bernhard L.A.
Highlights: Analytical formulae for verification of serviceability limits are derived. Rebars crossing the neck of reinforced concrete hinges are accounted for. Cracking beyond half of the width of the neck is accepted because of the rebars. The usefulness of the formulae is demonstrated based on experimental data. Eurocode-compatible design recommendations are elaborated and exemplarily applied. Abstract: Concrete hinges are monolithic necks in reinforced concrete structures. The serviceability limit states addressed herein refer to the open question how to limit tolerable relative rotations as a function of the compressive normal force transmitted across the neck. Analytical formulae are derived in the framework of the Bernoulli-Euler hypothesis and of Hooke's law. The usefulness of corresponding dimensionless design diagrams is assessed based on experimental data taken from the literature and on new results from structural testing of reinforced concrete hinges. This way, it is shown that the proposed mechanical model is suitable for describing serviceability limit states. Corresponding design recommendations are elaborated and exemplarily applied to verification of serviceability limit states of the reinforced concrete hinges of a recently built integral bridge. Because the reinforcement is explicitly accounted for, the tolerable relative rotations are larger than those according to the guidelines of Leonhardt and Reimann. Bending-induced tensile macrocracking beyond one half of the smallest cross-section of the neck is acceptable, because the tensile forces carried by the reinforcement ensure the required position stability of the hinges.